The efficacy of the inhalation of an aerosolized Group A streptococcal preparation in the treatment of lung cancer - Liu, Jun; Liu, Xiang; Cui, Fei; Chen, Guoqin; Guan, Yubao; He, Jianxing (Chinese Journal of Cancer Research; Vol 24, No 4 (December 07, 2012): Chinese Journal of Cancer Research, 2012)
Objective: To observe the efficacy of the inhalation of an aerosolized group A streptococcal (GAS) preparation in treating orthotopic lung cancer in mouse models and assess the feasibility, safety, and effectiveness of this administration mode for lung cancer. Methods: Lewis lung carcinoma (LLC) cell strains were administered via intrathoracic injection to establish orthotopic lung cancer mouse models. After the tumor-bearing models were successfully established, as confirmed by computed tomography, the mice were administered by inhalation with an aerosolized GAS preparation (GAS group) or aerosolized normal saline (control group). The anti-tumor effect of the aerosolized GAS preparation was evaluated histologically; meanwhile, the survival and quality of life were compared between these two groups. Results: The aerosolized GAS preparation showed remarkably anti-tumor effect, causing the necrosis of the orthotopic lung cancer cells in tumor-bearing mice. Furthermore, mice in the GAS group had significantly better quality of life and longer survival than those in control group. Conclusions: The inhalation of aerosolized GAS preparation may be a feasible, safe and effective solution for lung cancer.